A Comprehensive Juristic and Applied Study of Ijarah Muntahia Bittamleek - Syed Zia Ud Din; Prof. Dr.Radwan Jamal Yousef Elatrash (Journal of Religion and Society, 2025)
Ijarah Muntahia Bittamleek represents a significant and evolving contract within Islamic finance, aiming to reconcile modern economic needs with Shariah principles. Under this arrangement, an asset is leased for a specified period against agreed rental payments, and ownership is transferred to the lessee at the end of the lease through a separate and independent Shariah-compliant contract. This paper provides a comprehensive analysis of the juristic foundations, contemporary applications, and Shariah challenges associated with Ijarah Muntahia Bittamleek. Drawing upon classical Islamic jurisprudence, contemporary fiqh resolutions, and modern Islamic banking practices, the study establishes that the contract is fundamentally permissible, provided that the lease and ownership transfer remain distinct and that Shariah conditions are strictly observed. The findings and recommendations presented aim to guide Islamic financial institutions toward more authentic and compliant implementations. Keywords: Ijarah, Ijarah Muntahia Bittamleek, Islamic Finance, Lease-to-Own, Shariah Evaluation